From rehabilitation to remission in ankylosing spondylitis - A. Spadaro; E. Lubrano (PAGEPress Publications, 2011)
During the past years, exercise and non-steroidal anti-inflammatory drugs (NSAIDs) have been the mainstay of symptom control for Ankylosing Spondylitis (AS), a chronic, inflammatory rheumatic disease characterized by inflammatory back pain due to sacroiliitis and spondylitis. The ASsessment in AS (ASAS) international working group has constructed evidence based recommendations to guide the physician in the management of AS (1). Among the major recommendations for the management of AS, the ASAS group stated that there is a level Ib evidence that NSAIDs improve spinal pain, peripheral joint pain, and function, but comparative studies (1) or population-based survey (2) of different NSAIDs/coxib have not demonstrated one preparation to be clearly better than the others. Wanders et al (3) showed that the clinical efficacy of continuous NSAIDs/coxib treatment for AS was similar to intermittent ''on demand'' use and they suggested that the continuous treatment with NSAIDs/coxib could slow the radiographic disease progression over 2 years...